Analisis Viktimologis Terhadap Anak Sebagai Korban Penyalahgunaan Narkotika - Andi Suryani (Journal of Innovative and Creativity, 2025)
This study aims to analyze the implications for children who become victims of drug abuse and efforts to address these issues. The type of research used is empirical normative legal research. The normative legal approach, namely, legislation on narcotics crimes and child protection, with the addition of empirical elements in the form of direct interviews. The research data was systematically compiled and analyzed in accordance with empirical normative research methods. The results show that (1) the implications for children who become victims of drug abuse include damage to physical health, mental health, family life, social life, public order and security, and addiction. (2) Efforts to address these issues include preventive and repressive measures. This is done to restore the child's condition and is one way to provide legal protection for them.